2019
DOI: 10.1016/j.omtn.2019.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA-Enriched Vesicles Secreted by Hypoxic Cardiomyocytes Drive Cardiac Fibrosis

Abstract: Long non-coding RNAs (lncRNAs) have potential as novel therapeutic targets in cardiovascular diseases, but detailed information about the intercellular lncRNA shuttling mechanisms in the heart is lacking. Here, we report an important novel crosstalk between cardiomyocytes and fibroblasts mediated by the transfer of lncRNA-enriched extracellular vesicles (EVs) in the context of cardiac ischemia. lncRNA profiling identified two hypoxia-sensitive lncRNAs: ENSMUST00000122745 was predominantly found in small EVs, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 35 publications
0
89
0
Order By: Relevance
“…Hypoxic cardiomyocyte-derived EVs were taken up by fibroblasts and induced expression of profibrotic genes by these cells. 74 homolog/Akt pathway, whereas CPC-derived exosomes from healthy donors attenuated cardiac dysfunction. 77 Also, exosomes from nondiabetic rats protected primary rat cardiomyocytes from hypoxia/ reoxygenation injury via activation of the ERK1/2 and HSP27 pathway, 44 whereas exosomes from Goto Kakizaki type II diabetic rats lacked this ability.…”
Section: Hypoxia and Exosome Functionalitymentioning
confidence: 97%
“…Hypoxic cardiomyocyte-derived EVs were taken up by fibroblasts and induced expression of profibrotic genes by these cells. 74 homolog/Akt pathway, whereas CPC-derived exosomes from healthy donors attenuated cardiac dysfunction. 77 Also, exosomes from nondiabetic rats protected primary rat cardiomyocytes from hypoxia/ reoxygenation injury via activation of the ERK1/2 and HSP27 pathway, 44 whereas exosomes from Goto Kakizaki type II diabetic rats lacked this ability.…”
Section: Hypoxia and Exosome Functionalitymentioning
confidence: 97%
“…Kenneweg et al [ 101 ] showed lncRNA-enriched EVs in cardiac ischemia. In this context, lncRNA Neat1 was necessary for fibroblast and cardiomyocyte survival, and the silencing of Neat1 resulted in reduced heart function after myocardial infarction.…”
Section: Extracellular Vesicle As Biomarkers In Cvdmentioning
confidence: 99%
“…120 Moreover, NEAT1 was enriched in large extracellular vesicles secreted by hypoxic cardiomyocytes, which were taken up by fibroblasts, causing the expression of profibrotic genes. 121 However, it has not been reported whether NEAT1 exists in exosomes secreted by liver cells and whether exosome NEAT1 has a certain effect on mediating cellular communications in liver diseases, regardless of origin from the liver or other distant organs. Given that circulating NEAT1 may become a potential biomarker in several liver diseases, it is necessary for future investigators to detect NEAT1 expression in plasma exosomes.…”
Section: Con Clus I On and Future Pros Pec Tsmentioning
confidence: 99%
“…Notably, NEAT1 was also identified as an exosomal lncRNA, inhibition of which could influence inflammatory responses in inflammatory bowel disease (IBD) through exosome‐mediated polarization of macrophages 120 . Moreover, NEAT1 was enriched in large extracellular vesicles secreted by hypoxic cardiomyocytes, which were taken up by fibroblasts, causing the expression of profibrotic genes 121 . However, it has not been reported whether NEAT1 exists in exosomes secreted by liver cells and whether exosome NEAT1 has a certain effect on mediating cellular communications in liver diseases, regardless of origin from the liver or other distant organs.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%